PENGARUH LATIHAN SIDE HOP TERHADAP POWER OTOT TUNGKAI PADA PERMAINAN BOLA VOLI TEAM ANJUNGAN PEKANBARU - Nur Anshori Ruhayati; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is lack of power of leg muscles when carring out smash in volleyball game of Anjungan team Pekanbaru. According to that problem the writer conduct Side Hop exercise, to know the effect of Side Hop exercise toward power of leg muscle in volleyball game of Anjungan team Pekanbaru in order that, smash jump reach maximal jump. This reasearch is an experimental research, research design is one group pretest-posttest. The population is volleyball player of Anjungan team Pekanbaru which consist of 14 people. Technique sampling that is used is total sampling which is all population become people team volleyball Anjungan Pekanbaru. The instrument that is given is vertical jump test. After that the data is analyze with statistical way to test the normality with lilifors test on significant phase α (0,05). The Hyphotesis that is proposed is there is effect Side Hop exercise toward the power of leg muscle. Based on the results of the analysis resulted in pretest vertical jump the average of 46,43 and the average posttest of 51,93 with an increase of 5,5. According to T test, produce a result thitung 4,62 and ttable 1,771, it means that thitung > ttable . Therefore, there is effect Side Hop excercise toward power of leg muscle in volleyball of Anjungan Team PekanbaruKeywords : Side Hop, Power of leg muscles